Comment on ''A Modular Framework for Modeling Unsaturated Soil Hydraulic Properties Over the Full Moisture Range" by Weber et al. Issue 7 (20th July 2021) - Peters, Andre; Iden, Sascha C.
Abstract: Weber et al. (2019) (W19 in the following) present a modular framework for parametrizing soil hydraulic properties. The W19 model framework is almost identical to the model system developed jointly by Peters (2013), https://doi.org/10.1002/wrcr.20548, Iden and Durner (2014), https://doi.org/10.1002/2014wr015937, and Peters (2014), https://doi.org/10.1002/2014wr016107, to which we will refer as PDI ("Peters‐Durner‐Iden") model in the following. The primary goal of this comment is to uncover some inconsistencies of the W19 formulation. In the following, we (i) comment on the statement made by W19 regarding the number of parameters in the original PDI formulation, (ii) critically analyze the use of their function to parameterize the water retention curve (WRC), and (iii) show that, in contrast to the statement in W19, using their formulation of for parametrizing noncapillary hydraulic conductivity leads to systematic deviations from the physically based film‐conductivity model developed by Tokunaga (2009), https://doi.org/10.1029/2009wr007734 . Key Points: Non‐capillary parts of the hydraulic functions of Weber et al. (2019) are analysed Saturation function often agrees neither with experimental data nor with theoretical considerations Contrary to the authors' claim, the hydraulic conductivity function does not agree with Tokunaga's film‐flow model